2018
DOI: 10.1007/s00508-018-1411-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of native myocardial T1 and T2 mapping at 1.5T and 3T in healthy volunteers

Abstract: Summary Background Myocardial native T1 and T2 mapping are promising techniques for quantitative assessment of diffuse myocardial pathologies; however, due to conflicting data regarding normal values, routine clinical implementation of this method is still challenging. Methods To evaluate this situation during daily clinical practice the characteristics of normal values obtained in 60 healthy volunteers who underwent magnetic resonance imaging (MRI) scans o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

12
60
2
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 59 publications
(76 citation statements)
references
References 41 publications
(66 reference statements)
12
60
2
2
Order By: Relevance
“…7 Native T 1 reference values are higher for 3T than 1.5T scanners 10,11 and depend on the scanning sequence used with highest values for SASHA and lowest for ShMOLLI, with the MOLLI technique (as used in this study) in between. Some studies did not find any difference in native T 1 relaxation time according to sex 3,17 or age, 3,16 while others reported that age influenced T 1 values only in females. 14,16 There is, however, a large discrepancy between the results of those studies, which can be influenced by the type of sequence and scanner used.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…7 Native T 1 reference values are higher for 3T than 1.5T scanners 10,11 and depend on the scanning sequence used with highest values for SASHA and lowest for ShMOLLI, with the MOLLI technique (as used in this study) in between. Some studies did not find any difference in native T 1 relaxation time according to sex 3,17 or age, 3,16 while others reported that age influenced T 1 values only in females. 14,16 There is, however, a large discrepancy between the results of those studies, which can be influenced by the type of sequence and scanner used.…”
Section: Discussionmentioning
confidence: 96%
“…Some studies did not find any difference in native T 1 relaxation time according to sex 3,17 or age, 3,16 while others reported that age influenced T 1 values only in females. 16 Until now, it was unknown whether pubertal status could influence T 1 and T 2 relaxation times. 17 Even less is known in relation to T 2 relaxation time values, which were reported to be higher in females, 16 to decrease with age, 13 and with lowering heart rate.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations